Development and application of a model for assessing climate-related disaster risk. (15th October 2022) - Yu, Insang
Abstract: About USD 3542 million was caused by climate-related disasters during 2011–2020 in Republic of Korea. Risk area determination and cause analysis through risk assessment are essential for disaster risk reduction. Previous studies in Republic of Korea has assessed risk according to administrative district due to limitations in analysis of spatially extensive disaster impact and constructing geospatial data. This study developed and applied a model to assess gridded risk integrating various climate-related disasters in Daegu, Ulsan, Gyeongbook, and Gangwon of Republic of Korea. The developing process consists of design, implementation, and verification stage. The method of assessing risk using proxy variables was applied to the model. Gridded hazards constructed through numerical analysis, exposure, and vulnerability in high-resolution were utilized as input data. The model was verified by analyzing whether the observed damage was located within the upper and lower outliers of the gridded risk. The observed damage in 43 out of 54 (80%) administrative districts was located within the outlier range of gridded risk. Climate-related disaster risk was highest in the central region of Gangwon, which was highly affected by flood and snow risk. In Daegu and Ulsan, the flood risk was high in the low-lying area near the Nakdong and Taehwa rivers due to the concentration of population, building, and infrastructure. The model will be useful for central government, which requires integrated disaster risk information. Gridded risk can be used to determine hot spots in high-resolution for establishing strategies for disaster risk reduction and climate change adaptation of local government.